Automatic shape adjustment at joints for the implicit skinning. (February 2022) - Hachette, Olivier; Canezin, Florian; Vaillant, Rodolphe; Mellado, Nicolas; Barthe, Loïc
Abstract: The implicit skinning is a geometric interactive skinning method, for skeleton-based animations, enabling plausible deformations at joints while resolving skin self-collisions. Even though requiring a few user interactions to be adequately parameterized, some efforts have to be spent on the edition of the shapes at joints In this research, we introduce a dedicated optimization framework for automatically adjusting the shape of the surfaces generating the deformations at joints when they are rotated during an animation. This approach directly fits in the implicit skinning pipeline and it has no impact on the algorithm performance during animation. Starting from the mesh partition of the mesh representing the animated character, we propose a dedicated hole filling algorithm based on a particle system and a power crust meshing. We then introduce a procedure optimizing the shape of the filled mesh when it rotates at the joint level. This automatically generates plausible skin deformation when joints are rotated without the need of extra user editing. Graphical abstract: Highlights: We introduce a dedicated optimization framework for joints. It adjusts shape of the surfaces for the animation. A dedicated hole-filling algorithm is used on the initial mesh partition. The hole-filling is based on a particle system and power crust meshing. We introduce a procedure optimizing the shape of the filled mesh. This automatically generates plausible skin deformation when joints are rotated. This approach directly fits in the implicit skinning pipeline.